Biodiversity Portal of the Northern Part of West Siberia, Russia - Filippova, Nina; Filippov, Ilya; Ivanova, Natalya (Biodiversity Information Science and Standards, 2019)
Biodiversity-related studies in the northern part of West Siberia are relatively recent in line with intensive industrial development of the region in recent decades. The region possesses few biological collections within the universities and nature reserves. Still, the Department of Natural Resources pays considerable attention to the sustainable use of natural resources. On the global scale, the success of biodiversity informatics goals largely depends on the local initiatives and progress in data mobilization and sharing. Therefore, organization of regional biodiversity portals is important to promote data mobilization, education and citizen science on local scale. Previous experience of biodiversity information systems in the region was low. The program on digitization of observations of Red Listed species was launched in 2010 under the support of the Department of Natural Resources of Yugra. The information system for Red Listed species registrations was developed through this project and currently includes about three thousand observations. Another example of digitization in Western Siberia was developed by the biological collection of Yugra State University. Its database is based on the database management system Specify and available online through its web portal (http://bioportal.ugrasu.ru). Some collections of nature reserves have their catalogues in digital form. The need of biodiversity data mobilization is well understood and is discussed at regular workshops on biological collections management held in Khanty-Mansiysk. Recently, the biologists curating several biological collections in the region started a project on a regional biodiversity portal development (https://nwsbios.org). The portal has three major components: the database of collections based on Specify software (http://bioportal.ugrasu.ru), the metadata of different sources of biodiversity information in the region, an educational platform for learning biodiversity informatics, using data published via GBIF and DwC standards. This ...